2017
DOI: 10.5114/aoms.2017.66022
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous drug use – an independent predictor for HCV genotypes 3 and 4 infection among HIV/HCV co-infected patients

Abstract: IntroductionAbout one quarter of human immunodeficiency virus (HIV) infected persons in Serbia have also been found to be hepatitis C virus (HCV) co-infected. In the general population, HCV genotype 1 has been shown to be the most prevalent one. Here, we present the first study on the distribution of HCV genotypes among HIV/HCV co-infected patients in Serbia, in relation to epidemiological and clinical features.Material and methodsThe study included HIV/HCV co-infected and a group of HCV mono-infected patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Although considered as low prevalence country, the number of new cases is constantly growing and the epidemic in Serbia is among the most abundant in the region [77]. Clinical features and outcome of HIV infection in Serbia have been reported [78,79], however, very few studies have addressed different aspects of co-infection with hepatitis viruses [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Although considered as low prevalence country, the number of new cases is constantly growing and the epidemic in Serbia is among the most abundant in the region [77]. Clinical features and outcome of HIV infection in Serbia have been reported [78,79], however, very few studies have addressed different aspects of co-infection with hepatitis viruses [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that estrogen suppresses the intra-thymic T-cell differentiation while activating the extra-thymic pathways during pregnancy [80, [44,45] In the general population of Serbia about one quarter of human immunodeficiency virus (HIV) infected persons also have HCV coinfection [46] Asia The highest prevalence of HCV is noted in Central Asia (3.8%), East Asia (3.7%), and North Africa/Middle East (3.6%) [47,48] -Saudi Arabia [35,36,49] 0.7% -Yemen [37] 8.5% -Syria, Jordan and Lebanon [35] No data This reflects underestimation of the magnitude of the problem in this region [35] Iraq [38] 3.21% -Egypt [50,51] 8.6% Egypt is one of the areas of highest prevalence of HCV among the population in general and pregnant women in particular [50,51] with genotype 4 being predominant (90%) [52] Sudan [53][54][55] 0.6% Prevalence in pregnant women (0.6%) is lower than that of the general population (2.2-3.0%) [53][54][55] Libya and Maghreb region Lowest in Libya [56][57][58] (< 1%), followed by Tunisia [59][60][61][62], the Kingdom of Morocco [59,63], Algeria [59], and Mauritania [64][65][66] Genotype 4 is the most prevalent in Libya, which is the same as in Egypt, while genotype 1 [57,61,…”
Section: Natural History Of Hcv Infection In Infected Pregnant Womenmentioning
confidence: 99%
“…Infection with HCV genotype 2 is mainly associated with nosocomial transmission and prior dental treatment[ 1 , 22 ]. Genotype 3 is frequently found in the intravenous drug user communities and in those with history of tattooing and piercing[ 24 , 31 , 32 ]. Genotype 4 is mainly transmitted through high-risk sexual practices, especially among homosexual males, and intravenous drug use[ 1 , 22 ].…”
Section: Hcvmentioning
confidence: 99%